A Review of Preparation Methods and Strengthening Mechanisms of AlCoCrFeNi-Based High-Entropy Alloys - Li, Zhe (International Journal of Materials Science and Technology Studies, 2025)
This paper reviews the development, preparation methods, and strengthening mechanisms of high-entropy alloys (HEAs). Different from traditional alloys, HEAs contain at least five principal elements and show severe lattice distortion and chemical short-range order. These features give HEAs special mechanical properties. The article first introduces the background and research status of HEAs, especially the AlCoCrFeNi system. Then, it summarizes common preparation methods, such as vacuum melting, powder metallurgy, laser cladding, and high-temperature high-pressure sintering. After that, it discusses five main strengthening mechanisms: second-phase strengthening, work hardening, grain refinement, heterostructure strengthening, and solid-solution strengthening (substitutional and interstitial). Finally, it points out that the interstitial strengthening mechanism is still unclear, and more work is needed on composition design, heat treatment, and the cooperation among different strengthening methods. Further study on HEAs will provide new ideas for designing high-performance materials.